THE PLACE OF JALALUDDIN RUMI’S WORKS IN CONTEMPORARY SUFISM PHILOSOPHY - Samatov Jonmurod (Journal Park Publishing, 2025)
This article explores the significant role of Jalaluddin Rumi’s works in contemporary Sufi philosophy. Rumi, a prominent 13th-century Persian mystic and poet, laid the foundation for many key concepts in Sufism, such as divine love (ishq), spiritual journey (safar), inner purification, and union with the Divine (fana). His teachings, especially in his masterpiece Masnavi, continue to influence modern spiritual thought, offering insights into the human soul, the nature of divine reality, and the path of self-realization. In the context of contemporary Sufism, Rumi’s works bridge the gap between classical Islamic mysticism and modern spiritual practices, providing timeless wisdom on the importance of inner transformation, unity with the Divine, and the harmonious development of the self. This article will analyze how Rumi’s ideas are applied and adapted in today’s Sufi thought, especially in the light of challenges posed by the modern world.
Keywords: Jalaluddin Rumi, Sufism, contemporary philosophy, spiritual journey, divine love, inner purification, fana (annihilation in God), Masnavi, Islamic mysticism, self-realization, unity with the Divine, modern spiritual thought.